SISTEM RESERVASI ONLINE RUMAH SAKIT SEBAGAI SOLUSI ANTRIAN PADAT DI RSUD WARAS WIRIS BOYOLALI - M. Nuraminudin; Airlangga Aditya Nugraha (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Every human being needs health facilities, both for those who really suffer from an illness or someone who only needs regular health checks. One of them is RSUD Waras Wiris Boyolali which is always crowded with patients. In view of the situation and conditions of the world that have been and are still dealing with viruses that spread easily such as Covid-19, the crowded and crowded conditions of these patients are very dangerous. Therefore, an online hospital reservation system was designed with the aim of making it easier to schedule patient arrivals to the hospital. With this online reservation system, patients do not need to wait in crowds in the hospital waiting room. The system created is based on the Android operating system which is widely used by patients so it is easy to use. The research method used uses the waterfall method which starts from the process of analysis, design, to implementation so that this system is expected to be in accordance with the needs of hospitals and hospital patients, especially to handle patient queuing processes.